2-9b+3=

Simple and best practice solution for 2-9b+3= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2-9b+3= equation:


Simplifying
2 + -9b + 3 = 0

Reorder the terms:
2 + 3 + -9b = 0

Combine like terms: 2 + 3 = 5
5 + -9b = 0

Solving
5 + -9b = 0

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5 + -9b = 0 + -5

Combine like terms: 5 + -5 = 0
0 + -9b = 0 + -5
-9b = 0 + -5

Combine like terms: 0 + -5 = -5
-9b = -5

Divide each side by '-9'.
b = 0.5555555556

Simplifying
b = 0.5555555556

See similar equations:

| 5r-(2r+8)=18 | | 2s-9s+7= | | -12/1.8=c | | 15x-21=219 | | -121+64=0 | | 7-8g-6= | | 6x+4=4(x+8) | | 7-6c+9c= | | 8m+19=9m+11 | | (x+1)/3+4=(x+7)/9 | | -3x+5x+5=11 | | 38-8x+x^2=0 | | 8+3g-2= | | 9(t+2)=2(t-2) | | -2x-4y=0 | | 10-y=2x+3 | | 3+x-14=20 | | 69-45= | | -5x-20y=-15 | | -4(w-5)=3w+6 | | 24-6n=8(7n+3) | | (3n+9)-(2n+4)= | | -506-(576)= | | 2x+8=30x+10 | | 5y-1+y+47=6+6y+44-2y | | (-n+(-3))-(8n+(-2))= | | 12b+5=b-303 | | 13x^2+10x-3=0 | | a=(x-2)(x-1) | | (8n+4)-(n+(-2))= | | 5m+4m-28=45 | | 24-4x=15x |

Equations solver categories